Robust ultraclean atomically thin membranes for atomic-resolution electron microscopy - Liming Zheng (Nature Portfolio, 2020)
High-resolution electron microscopy requires robust and noise-free substrates to support the specimens. Here, the authors present a polymer- and transfer-free direct-etching method for fabrication of graphene grids with ultraclean surfaces and demonstrate cryo-EM at record high resolution.